Integrated transcriptome and plant growth substance profiles to identify the regulatory factors involved in floral sex differentiation in Zanthoxylum armatum DC - Hui, Wenkai; Fan, Jiangtao; Liu, Xianzhi; Zhao, Feiyan; Saba, Tasheen; Wang, Jingyan; Wu, Aimin; Zhang, Xuebin; Zhang, Junli; Zhong, Yu; Chen, Gang; Gong, Wei (Frontiers in Plant Science, 2022)
Zanthoxylum armatum is a prominent plant for food industries. Its male flowers often occur in gynogenesis plants, however, the potential mechanism remains poorly understood. Herein, a total of 26 floral sex differentiation stages were observed to select four vital phases to reveal key factors by using RNA-seq, phytohormones and carbohydrates investigation. The results showed that a selective abortion of stamen or pistil primordia could result in the floral sex differentiation in Z. armatum. Carbohydrates might collaborate with cytokinin to effect the male floral differentiation, whereas female floral differentiation was involved in SA, GA1, and ABA biosynthesis and signal transduction pathways. Meanwhile, these endogenous regulators associated with reproductive growth might be integrated into ABCDE model to regulate the floral organ differentiation in Z. armatum. Furthermore, the 21 crucial candidates were identified in co-expression network, which would contribute to uncovering their roles in floral sex differentiation of Z. armatum in further studies. To the best of our knowledge, this study was the first comprehensive investigation to link floral sex differentiation with multi-level endogenous regulatory factors in Z. armatum. It also provided new insights to explore the regulatory mechanism of floral sex differentiation, which would be benefited to cultivate high-yield varieties in Z. armatum.